The effects of PGV-1 and PGV-2 on the b-hexosaminidase release from intraceluller calcium ion-induced mast cells - Agung Nugroho (Indonesian Journal of Pharmacy, 2009)
PGV-1 or 2,5-bis(4'-hydroxy-3',5'-dimethylbenzylidene)cyclopentanone and PGV-2 or 2,5-bis(4'-hydroxy-3',5'-diethylbenzylidene)cyclopentanone are two benzylidene cyclopentanone analogues of curcumin. In our study, weinvestigated the effects of these compounds on the b-hexoaminidase enzyme release from mast cell culture (RBL-2H3 cell line). Thapsigargin and ionomycin were used as intracellular calcium ion stimulants for inducing b-hexoaminidase enzyme release from mast cells. The release of b-hexoaminidase enzyme was determined by colorimetric methods with substrate, p-nitrophenyl-2-acetamido-2-deoxy-b-D-glucopyranocide, and a microplate reader at 405 nm. In present study, treatment of 0.5 mM thapsigargin or 1 mM ionomycin could stimulate therelease of b-hexoaminidase enzyme from RBL-2H3 cells by 43.91 ± 1.30 % dan 52.93 ± 2.07 %, respectively. PGV-1 and PGV-2 showed inhibitory effects on the b-hexoaminidase enzyme release from RBL-2H3 cells induced by the increase of intraceluller calcium ion in dose-dependent manner. At the dose of 100 mM, PGV-1 and PGV-2, respectively, inhibited the b-hexoaminidase enzyme release by 73.51 ± 8.69 % and 66.42 ± 8.63 % on thapsigargin experiments; and by 89.73 ± 3.23 % and 38.57 ± 5.32 % on ionomycin experiments. The IC50 values of their effects on the b-hexoaminidase enzyme release from RBL-2H3 cells, respectively, were 22.20 mM and 22.27 mM on thapsigargin experiment; and 22.77 mM and >100 mM on ionomycin experiment. Based on the results, the inhibitory effect of PGV-1 and PGV-2 on the b-hexoaminidase enzyme release from RBL-2H3 cells involving mechanisms related to the alteration on activationprocesses of intracellular calcium ion on mast cells.Key words : Curcumin, PGV-1, PGV-2, mast cells, b-hexoaminidase enzyme